Highly sensitive methyl parathion sensor based on Au-ZrO2 nanocomposites modified graphene electrochemical transistor. (10th October 2020) - Tao, Tian; Zhou, Yang; He, Chaohui; He, Hanping; Ma, Mingyu; Cai, Zhiwei; Gao, Nan; Wang, Kai; Zhu, Ruizhi; Chang, Gang; Liu, Zhihua; He, Yunbin
Highlights: The GECT was designed and fabricated for the detection of MP for the first time. Au-ZrO2 nanocomposites were successfully co-deposited on graphene channel. Low detection limit (0.1 ng/mL) and ultra-wide linear (4 × 10 −4 –7 μg/mL) were obtained. The sensor has promising practicality for its good selectivity toward interferents. The sensor showed excellent recovery results of MP in Chinese cabbages. Abstract: The excessive use of pesticides does great harm to environment and human health, a high performance sensor is urgently needed for the management of pesticides contamination. Herein, a novel graphene electrochemical transistor (GECT) for the detection of methyl parathion (MP) was successfully fabricated for the first time. A single layer of graphene was covered between the source and drain electrodes by the wet transfer method to act as channel for the transistor. Au-ZrO2 nanocomposites were electrodeposited at graphene channel of the device, considering the special affinity of ZrO2 nanoparticles toward phosphate group and electrocatalytic ability of Au nanoparticles. The sensing mechanism was attributed to the change of carrier concentration in channel induced by the electrochemical reaction of MP at the graphene channel, which built up the mathematic relationship between the change of channel current and the concentration of MP. Different modified materials and electrodeposition conditions were compared and optimized. Due to the high carrier mobility of graphene and excellent catalytic performance of Au-ZrO2 nanocomposites in the channel, the developed sensor showed a limit of detection as low as 0.1 ng/mL and ultra-wide linear range from 0.4 ng/mL to 7 μg/mL, which are comparable or superior to those using the large-scale instruments. Meanwhile, the device exhibited good selectivity toward usual interferents and high accuracy for detection of MP in Chinese cabbage samples, demonstrating the promising practicality of the devices. It is expected that GECT can act as a desirable transducer platform for highly sensitive and selective detection of pesticides. Graphical abstract: A novel graphene electrochemical transistor based on Au-ZrO2 nanocomposites is fabricated for the highly sensitive detection of methyl parathion. Image, graphical abstract